KONDİLEKTOMİ VE SİLİKON İNTERPOZİSYONU İLE TEDAVİ EDİLEN 32 ÇENE ANKİLOZUNUN UZUN TAKİP SONUÇLARI - AYDIN, Yağmur; GÜZEL, M. Zeki; ÇINAR, Can (Cerrahpaşa Medical Journal, 2019)
Background.- Temporomandibular joint ankylosis, usually secondary to trauma, leads to both functional and aesthetic problems. The surgical treatment of such cases is usually challenging problem to the reconstructive surgeon. The main goals of treatment are to restore Temporomandibular joint function so that patients would be able to open their mouths in order to maintain essential functions such as nutrition, oral hygiene, chewing, and speech and to prevent patients from recurrence. Condilectomy, condilectomy with coronoidectomy, and silicone interpositon are commonly used to treat this pathology. Design.- 11 bilateral and 10 unilateral temporomandibular joint ankylosis were treated with condilectomy and silicone interposition between 1988 and 1998. The surgical goal was to achieve at least 3.5-cm.of interincisal opening. For this purpose, all patients underwent condilectomy. When condilectomy was inefficient, coronoidectomy with/without soft tissue stripping was performed. Resultant defect was filled with custom-made silicone bloc. Results.- Patients were followed 12 years (mean 7 years). No complication was seen during the follow-up period. The overall results were satisfactory in all patients. Only one patient who had undergone three unsuccessful surgical interventions before our treatment necessitated second surgical correction with the same technique due to the recurrence. Conclusion.- Condilectomy, if necessary, coronoidectomy combined with silicone interposition is highly effective surgical technique to treat TMJ ankylosis especially in adult patients presenting recurrent disease and having this pathology for a long time. We also suggest that at least 3.5 cm interincisal opening be obtained in operation to ensure the satisfactory result.